Jianpi Huayu Decoction Attenuates the Immunosuppressive Status of H22 Hepatocellular Carcinoma-Bearing Mice: By Targeting Myeloid-Derived Suppressor Cells - Xie, Yingjie; Zhang, Yuan; Wei, Xiaohan; Zhou, Cheng; Huang, Yajing; Zhu, Xingwang; Chen, Yongxu; Wen, Huihong; Huang, Xuhui; Lin, Juze; Wang, Ziying; Ren, Yan; et al. (Frontiers in Pharmacology, 2020)
Tumor-induced immunosuppressive microenvironment in which myeloid-derived suppressor cells (MDSCs) plays an important role, remains an obstacle for effective oncotherapy currently. Inducing MDSCs into maturation was confirmed as an effective method to reduce the tumor-bearing host’s immunosuppression. Traditional Chinese medicines (TCM) possessed characteristics of alleviating immunosuppression of cancer patients and low toxicity. Jianpi Huayu Decoction (JHD) was an experienced compound of TCM for oncotherapy based on TCM theory and clinical practice. Our study was designed to further investigate the regulation of JHD on the immune system in the H22 liver-cancer mouse model. We found that JHD significantly reduced the destruction of spleen structure, immunosuppressive ability of MDSCs, proportion of Treg and Th17, and increased the proportion of CTL, DC and CD11b+Gr-1+cells in spleen, but with no significant change of Th1, Th2 and macrophage. In vitro experiments showed that apoptosis of MDSCs was decreased as the time of JHD stimulation increased, which partly explained the increase of CD11b+Gr-1+cells in the spleen. Meanwhile, JHD could promote the differentiation of MDSCs into macrophages and dendritic cells, attenuate expression of ROS in MDSCs and reduce its proliferative inhibition on CD4+ T cells, in vitro. Generally, JHD may be a complementary and alternative drug for attenuating the immunosuppressive status induced by hepatocellular carcinoma, possibly by promoting differentiation and inhibiting the immunosuppressive activity of MDSCs.